Intracranial Response of Brain Metastases to Osimertinib With or Without Upfront Stereotactic Radiosurgery in TKI-Naïve Nonsmall Cell Lung Cancer Patients. (1st September 2019) - Jin, Michael Chuwei; Liu, Elisa K; Macaulay, Charles W; Gian, Amanda; Shi, Siyu; Koenig, Julie; Li, Gordon; Soltys, Scott G; Pollom, Erqi L
Abstract: INTRODUCTION: Stereotactic radiosurgery (SRS) is an accepted standard of care for the treatment of brain metastases. However, the benefit of upfront SRS in combination with osimertinib, which has excellent intracranial penetrance, for patients with EGFR-mutant nonsmall cell lung cancer (NSCLC) is unknown. Improved understanding of brain metastasis dynamics in patients treated with osimertinib without intracranial radiotherapy (icRT) could provide insight into the additive benefit of upfront SRS. METHODS: This retrospective cohort study included TKI-naïve NSCLC patients with brain metastases treated with osimertinib between 2017 and 2019 at Stanford University. Mutation status was determined by next generation sequencing (NGS), digital droplet polymerase chain reaction (PCR), or EGFR sequencing. Serial brain magnetic resonance imaging (MRIs) were interrogated for intracranial progression and metastasis response. RESULTS: A total of 32 patients with 204 brain metastases were identified. A total of 16 patients received osimertinib with upfront icRT (15 SRS) while 16 received osimertinib alone. EGFR mutations were identified, with 17 patients receiving targeted NGS. Initial sizes of measurable brain metastases were similar in patients treated with icRT compared to those receiving osimertinib alone (median 4.5 mm vs 5.0 mm, P = .3813). Number of measurable brain metastases were similar (median 3.5 vs 5.5, P = .2322). A total of 11 (34.4%) patients experienced disease progression on osimertinib (8 [25%] intracranial, 7 [21.9%] extracranial). Changes in brain metastasis size of patients receiving osimertinib alone were assembled based on serial brain MRI. Although changes in metastasis size were not evident in the first MRI after starting osimertinib (Pscan1 = 0.4928), subsequent scans demonstrated increased stratification (Pscan2 = 0.0043 and Pscan3 = 0.0131). CONCLUSION: TKI-naïve NSCLC patients receiving osimertinib demonstrate good intracranial response. Understanding the dynamics of metastasis growth could help identify patients at risk for disease progression and those most likely to benefit from icRT.